Space-time transformations of urban landscapes of the city of Poltava - Shevchuk, S.; Hlukhota, V. (Scientific Progress & Innovations, 2024)
The city, as a geographical category, has historically served as a pivotal center and engine of social, scientific, and technological progress. It accumulates demographic, administrative, economic, scientific-technical, and cultural potential, exerting a profound and often decisive influence on the development of surrounding areas. The modern city has become a key hub of spatial transformations that radiate outward, affecting not only adjacent regions but also entire countries and continents. These transformations lead to the emergence of a unique type of landscape – the urbanlandscape. Contemporary landscape studies go beyond examining the structure and diversity of landscapes. They increasingly focus on forecasting the processes and phenomena characteristic of such environments. A central aspect of this research involves analyzing the transformation of natural landscapes into their modified forms, known as anthropogenic landscapes, which eventually evolve into urban landscapes. Unlike natural landscapes, the development and diversification of urban landscapes are ongoing and dynamic processes, reflecting the continuous interplay between human activity and the natural environment. In this study, the typology of urban landscapes has been expanded through the application of supervised classification techniques in Geographic Information Systems (GIS). This approach has enabled the identification of primary and secondary types of urban landscapes. The research traces the evolutionary trajectory of Poltava's urban landscape, starting from the earliest settlements in the region. This progression moves through the stages of anthropogenic landscapes, residential landscapes, and urban landscapes, culminating in the formation of highly urbanized landscapes, which represent the apex of this developmental process. The study also examines the geographical factors that have shaped Poltava’s urban landscapes and highlights the historical conditions underlying the city's emergence and development. A comparative analysis of satellite imagery from 1985 to 2023 reveals significant transformations in the city's urban landscapes over time. Among the most notable changes is the conversion of garden-park landscapes into low-rise urban landscapes. Simultaneously, high-rise urban landscapes have emerged in areas previously occupied by industrial urban landscapes. These shifts reflect broader trends of urban densification and spatial reorganization. Overall, the findings indicate a decrease in the area of garden-park landscapes, accompanied by a corresponding increase in both low-rise and high-rise urban landscapes. This transformation underscores the dynamic nature of urban development and its impact on the structure and function of urban landscapes. The study not only enhances our understanding of urbanlandscape evolution but also provides a framework for future urban planning and sustainable development in Poltava and similar cities.